Fondos aragoneses del Museo Lázaro Galdiano - Saguar Quer, Carlos (Artigrama, 2005)
La colección reunida por D. José Lázaro (1862-1947) destaca entre las colecciones españolas de su tiempo no sólo por la cantidad, calidad y variedad de sus fondos, sino también por su carácter cosmopolita. Entre las obras de procedencia aragonesa se encuentran piezas emblemáticas como el Ceremonial de la consagración y coronación de los reyes y reinas de Aragón, redactado por Pedro IV, o el sello de oro de Martín I, así como importantes piezas de platería, tablas góticas y lienzos de Goya. The collection gathered by José Lázaro (1862-1947) outstands amongst the Spanish collections of his time, not only because of the quantity, quality and variety of its funds, but also because of its cosmopolitan character. Among the works coming from Aragón, there are very emblematic pieces, such as the Kings and queens from Aragón consecration and coronation book of ceremonies, drawn up by Pedro the IVth, and Martin the Ist’s gold seal, as well as important silver pieces, gothic panels and canvas painted by Goya.